Discovery of Novel Viruses in Mosquitoes from the Zambezi Valley of Mozambique. - Harindranath Cholleti; Juliette Hayer; Ana Paula Abilio; Fernando Chanisso Mulandane; Jenny Verner-Carlsson; Kerstin I Falk; Jose M Fafetine; Mikael Berg; Anne-Lie Blomström (PLoS ONE, 2016)
Mosquitoes carry a wide variety of viruses that can cause vector-borne infectious diseases and affect both human and veterinary public health. Although Mozambique can be considered a hot spot for emerging infectious diseases due to factors such as a rich vector population and a close vector/human/wildlife interface, the viral flora in mosquitoes have not previously been investigated. In this study, viral metagenomics was employed to analyze the viral communities in Culex and Mansonia mosquitoes in the Zambezia province of Mozambique. Among the 1.7 and 2.6 million sequences produced from the Culex and Mansonia samples, respectively, 3269 and 983 reads were classified as viral sequences. Viruses belonging to the Flaviviridae, Rhabdoviridae and Iflaviridae families were detected, and different unclassified single- and double-stranded RNA viruses were also identified. A near complete genome of a flavivirus, tentatively named Cuacua virus, was obtained from the Mansonia mosquitoes. Phylogenetic analysis of this flavivirus, using the NS5 amino acid sequence, showed that it grouped with 'insect-specific' viruses and was most closely related to Nakiwogo virus previously identified in Uganda. Both mosquito genera had viral sequences related to Rhabdoviruses, and these were most closely related to Culex tritaeniorhynchus rhabdovirus (CTRV). The results from this study suggest that several viruses specific for insects belonging to, for example, the Flaviviridae and Rhabdoviridae families, as well as a number of unclassified RNA viruses, are present in mosquitoes in Mozambique.